Analysis of Atomic Force Microscopy Images of Crystal Originated “Particles” on Silicon Wafers Treated with NH4OH:H2O2:H2O Solution - Lee, W. P.; Seow, W. S.; Yow, H. K.; Tou, T. Y. (The Japan Society of Applied Physics, 2001)
Crystal-originated particle (COP) side-wall angles and rates of change in width were measured after treatment in an SC-1 solution by atomic force microscopy (AFM) to determine the shape, size and type of the particles on a polished (100) Si wafer surface. The etched silicon tip's maximum measurable slope angles were used to determine whether a COP originated from either the upper or the lower portion of an octahedral void. If the COP side-wall angle is equal to the maximum measurable slope angle of around 72 degrees, the COP originated from the upper portion of the void. The lower portion of an octahedral void corresponds to a side-wall angle of 55 degrees. This was confirmed through the study of COP width changes in NH4OH : H2O2 : H2O (SC-1) solution. The COP width depends on the rates of change in width and the shape of its void. The rates of change of width of the COP which originated from the lower portion of the void was found to be 0.8 nm/min whereas that of the COP which originated from the upper portion of the void was 2.5 nm/min. It is also shown that a perceived single-type COP could very well be the upper part of a twin-type COP, which reveals its form of a much larger geometry only after the wafers are dipped repeatedly in the SC-1 solution.